Variation of endophytic cork oak-associated fungal communities in relation to plant health and water stress (Forest Pathology, 2011)
The main objective of this study was to obtain more comprehensive knowledge about the eﬀect of water stress on endophytic fungal communities in asymptomatic and declining cork oak trees. Six asymptomatic and six declining cork oak trees were randomly selected in a natural cork oak forest located in Sardinia, Italy. In February 2003, the soil around three asymptomatic and three declining trees was covered with a circular plastic ﬁlm to reduce rain water supply with the intention to induce water stress. The remaining six trees served as controls. Predawn xylematic water potential (PWP) was used as water status indicator and measured seasonally. Between July 2003 and June 2004, fungal endophytes were isolated every 2–4 months from twigs, branches and woody tissues. Signiﬁcant diﬀerences in PWP between covered and control trees were detected mainly in autumn. Gas exchange was greatest in asymptomatic control plants. All tissues were colonized by endophytic fungi. Nineteen fungal species were isolated from 1620 plant fragments. Biscogniauxia mediterranea was the most frequently isolated fungus. Its isolation frequency was signiﬁcantly higher in declining covered trees than in control trees (p < 0.05). Presence of this fungus in asymptomatic control trees was signiﬁcantly higher in winter than in summer. Water stress seems to reduce species diversity of the endophytic mycobiota in cork oak and to promote proliferation of some potentially pathogenic endophytes.

Physiological responses of cork oak and holm oak to infection by fungal pathogens involved in oak decline (Forest Pathology, 2009)
The aim of this research was to study the changes in net photosynthesis and stomatal conductance values in 3-year-old cork oak and holm oak seedlings growing in natural conditions and inoculated with Apiognomonia quercina, Biscogniauxia mediterranea, Botryosphaeria corticola and Pleurophoma cava. Throughout the 4-month experimental period, the evolution of visual external symptoms and the values of physiological variables were periodically recorded. All pathogens caused stem lesions around the infection point; however, the lesions caused by B. corticola were longer in both oak species. On cork oak seedlings, all pathogens induced a signiﬁcant and gradual reduction in net photosynthesis and stomatal conductance values, whereas other physiological disturbances were induced only by B. corticola infections on holm oak seedlings.